The Consumption Patterns and Nutritional Status of Toddler in Wee Kombaka Village, Southwest Sumba District - Dadi, Reniwati N. D.; Aspatria, Utma; Ndun, Helga J. N. (Faculty of Public Health, Nusa Cendana University, 2022)
Malnutrition usually occurs in infants because at that age children are faced with rapid development. The purpose of this research is to describe the pattern of food consumption and nutritional status of toddler in Wee Kombaka Village. This type of research is descriptive qualitative. The time of the research was carried out in December 2020-February 2021. The sample obtained was 83 mothers who have toddler. The sampling method used was total sampling. The results showed that the age of the mother was at most 20-35 41.0%, the most educated were elementary school graduates 27.7%, working mothers were 65.1%, the number of family members was at most 54.2%, toddlers consumed the most porridge + fruit 42.3%, frequency of eating at most 54.2%, dietary restrictions at most 81.1%, proper form of eating at most 73.5%, history of exclusive breastfeeding at most not exclusive breastfeeding 65.1% , the most nutritional status was normal nutrition 59.1%. Cadre health officers stationed in Wee Kombaka Village are more active in providing counseling and correct food consumption patterns. Mothers of toddlers are more active in seeking information about good and correct consumption patterns for consumption by toddlers which will have an impact on the nutritional status of toddlers.